REVIEW OF YOHANES S. PURWADI'S “SOCIO-CULTURAL DIMENSION OF SCIENCE” - Wijaya, Irianto (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2008)
Whenever we claim that our idea is better than another idea, it is always important to have a good understanding of the ‘inferior’ idea and to be able to present our own one in a clear and coherent manner. The failure to do both will lead not only to a bad argument, but, more fatally, also to an unfair judgment of the idea we oppose.